Paleoinvironmental Reconstruction by Calcareous Algae at Paleocene – Early Eocene in North-East Iraq - Surdashy, Ali Mahmood (Sulaimani Journal for Pure and Applied Sciences, 2001)
The Paleocene — E. Eocene is typically rich in algae, consisting of wide selection of genera and species such as. Dasycladacean, Codiaceanc, Ethilia Parachaetes and, Archiolithotharninium, of back reef reef and fore reef. This carbonate sequence comprising the Sinjar, Khurmala, Walash Naupurdan Lst, Underlained by the flysch facies of kolosh, lower volcanic unit of and shally group Naupurdan. Tectonic events resulting in this facies inversion from deep environment to shallow algal carbonate over the large part of unstable shelf basin in Iraq. The contact between these two different facies is the border between two different tectonic stage, the _first one was the meogeosynclinal trough of Kolosh basin followed bay the second facies of epeiric shelf or ramp which Is the beginning of Molasse or post orogeny facies.